Risk Factors for Operating Room No‐Show in an Academic Otolaryngology Practice. (5th February 2022) - Trott, Skylar; Young, Rory; Hayden, Christopher; Yessin, Olivia; Bush, Matthew; Gupta, Nikita
Abstract : Objectives/Hypothesis: A no‐show to the operating room date negatively impacts a hospital and can lead to increased costs for an institution in terms of time, materials, and manpower. Our objectives are to identify the factors associated with operating room no‐shows in order to increase clinical efficiency, reduce hospital costs, and increase patient access to care. Study Design: Single institution retrospective chart review. Methods: A retrospective review was performed of all surgeries within the Otolaryngology department performed at a single tertiary academic center between 2006 and 2019. Demographic and surgical data were collected from the charts. Descriptive, univariate, and multivariate statistics were performed on the data. Results: There were a total of 1, 752 no‐shows and 46, 440 patients who did show with an overall no‐show rate of 3.63%. A multivariate logistic regression analysis was performed to compare patients who did not show for surgery to those who did. Analysis found multiple risk factors for not showing to surgery that were statistically significant ( P < .05) and included decreasing age, planned outpatient case, head and neck oncology subspecialty, increasing distance from the facility, higher number of clinic no‐shows, and not having private insurance. African‐American race was more likely to show for surgery as scheduled. Conclusions: Numerous factors may play a role on whether or not a patient attends a scheduled surgical date. Some of these factors may be preventable or modifiable to mitigate increased hospital costs associated with no‐show to surgery and increase access to care. Level of Evidence: 3 Laryngoscope, 132:1738–1742, 2022